The Effectiveness of a Digital Encyclopedia in Enhancing Scientific Literacy - Dewanti, Astrivia; Maryani, Ika (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to examine the effectiveness of using a digital encyclopedia to enhance students’ scientific literacy. In line with the rapid advancement of technology, the integration of digital media in the learning process has become increasingly relevant and essential. This research employed a quantitative experimental method using a one-group pre-test–post-test design. The sample was randomly selected from three classes, resulting in one experimental group. Data were collected through classroom observations and scientific literacy tests that had been previously validated. Data analysis involved a paired sample t-test to assess differences in scores before and after the intervention, and an effect size analysis using Cohen’s d to measure the magnitude of the impact. The results indicate that the use of a digital encyclopedia had a significant positive effect on improving students' scientific literacy. The engaging and interactive presentation of instructional materials proved effective in increasing students’ learning interest, which in turn fostered a culture of literacy. This study recommends further development of contextual digital learning media tailored to students’ educational levels.